Differential palliative care issues in patients with primary and secondary brain tumours - Christoph Ostgathe; Jan Gaertner; Maren Kotterba; Sebastian Klein; Gabriele Lindena; Friedemann Nauck; Lukas Radbruch; Raymond Voltz (2009)
Cancer may affect the central nervous system either by primary or secondary brain tumours (PBT/SBT). Specific needs of these patients and special requirements of services caring for them have not been adequately addressed so far. Since 1999, an annual, 3-month census is being conducted in different palliative care settings throughout Germany. Pooled data from the years 2002–2005 were analysed to test for differences between patients with PBT, SBT and other palliative care patients (OP). Symptom frequencies, ECOG status and nursing needs were tested for differences (χ²). Free text entries for reasons for admission were recorded, categorised and analysed descriptively. A total of 5,684 patients were documented (PBT n = 153, 2.7%; SBT n = 661, 11.9%; OP n = 4,872, 85.4%). For patients with PBT, poor functional status and high need for nursing support was reported more frequently than for patients with SBT and OP. For patients with PBT/SBT physical symptoms (pain, nausea, vomiting, constipation and loss of appetite) were documented less frequently and in lower intensity than for OP. However, nursing, psychological, and social problems/symptoms were documented significantly more often and showed higher intensity, particularly the patients'' need for support with the activities of daily living, disorientation/confusion of the patients and overburdening of the family. For 67% of all patients, a reason for admission was documented in free text. Main reasons were symptom control (OP>SBT>PBT), social issues (PBT>SBT>OP), functional deficits (PBT>SBT>OP) and cognitive impairment (PBT/SBT>OP). Distinct neurological deficits and problems were documented more often as secondary ICD-diagnoses than as a leading reason for admission. The specific palliative care problems and the rationales leading to health care utilisation point to the need for an appropriate interdisciplinary and multi-professional provision of care for patients with brain malignancies, with a particular view on the needs of the families and an early integration of social and psychological support.